"Por que tão poucas mulheres?": práticas de numeramento na eja em um cenário de investigação acerca da (dis)paridade de gênero na política - Frei Junior, Rubens Antonio (Universidade Federal de São Carlos, 2025)
This master thesis, developed within the scope of the Professional Graduate Program in Education at the Federal University of São Carlos, aims to understand the applications and implications of an intervention research through investigation scenarios in Critical Mathematics Education, with the perspective of identifying the numeracy practices mobilized by Youth and Adult Education students in the literacy phase. It is part of the knowledge production of "MANCALA – Study and Research Group in Mathematical Education, Culture and Teacher Training" (CNPq). The investigation was structured around the following question: What numeracy practices do youth and adult education students mobilize when faced with investigation scenarios based on everyday problems? The research was carried out with a multigrade Youth and Adult Education, class in a public school in Rio Claro – SP, composed of working students with trajectories marked by school interruptions, experiences of social exclusion, and limited familiarity with school mathematics. Data production and analysis adopted a qualitative approach, based on the principles of Critical Mathematics Education, Freireana Critical Education and studies on numeracy as a social practice. The proposed investigation scenarios had gender parity in Brazilian politics as a generative theme and sought to connect mathematical content to the concrete experiences of the students, provoking reflections on social inequalities and encouraging the exercise of critical reading of the world. The analysis was conducted based on the dialogues and strategies mobilized by the subjects to solve the proposed situations, considering both the mathematical procedures and the meanings attributed to the activities. The results show that, when placed in dialogical, critical, and situated contexts, Youth and Adult Education students demonstrate significant capacities to mobilize mathematical knowledge articulated with their life experiences. In this process, numeracy practices emerge as collective constructions that transcend the technical domain of mathematics, revealing diverse ways of interpreting, arguing, and acting upon reality. The research also points to the importance of the teacher assuming an investigative and reflective stance, capable of valuing students’ knowledge and enhancing their autonomy. This study contributes to the strengthening of pedagogical proposals that are more sensitive to the specificities of Youth and Adult Education, promoting a Critical Mathematics Education that is contextualized and emancipatory.
"Why so few women?": numeracy practices in eja in a research scenario on gender (dis)parity in politics
Keywords: Educação de Jovens e Adultos; Numeramento; Educação matemática crítica; Youth and Adult Education; Numeracy; Critical mathematical education; CIENCIAS HUMANAS::EDUCACAO